2015
DOI: 10.1121/1.4937759
|View full text |Cite
|
Sign up to set email alerts
|

Low-frequency beamforming for a miniaturized aperture three-by-three uniform rectangular array of acoustic vector sensors

Abstract: This paper proposes a mode domain beamforming method for a 3 × 3 uniform rectangular array of two-dimensional (2D) acoustic vector sensors with inter-sensor spacing much smaller than the wavelengths in the working frequency band. The acoustic modes are extracted from the particle velocity observations in light of the source-sink pictures of the Taylor's series multipoles [Wikswo and Swinney, J. Appl. Phys. 56(11), 3039-3049 (1984)]. Then, similar to other mode domain methods, the modes are synthesized to obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Then, the temperature difference can be converted into an electrical signal by a Wheatstone bridge. The perturbation temperature field δT can be solved by the following equation in the Cartesian coordinates [18] ∂ t δT − D∇ 2 δT = −v∂ x T (11) where D = k/ρcp is the heat diffusion coefficient of the air, and ∂xT is the gradient of the stationary temperature distribution. The temperature perturbation caused by a single heating wire is derived…”
Section: Temperature Perturbation Due To the Acoustic Wavementioning
confidence: 99%
See 1 more Smart Citation
“…Then, the temperature difference can be converted into an electrical signal by a Wheatstone bridge. The perturbation temperature field δT can be solved by the following equation in the Cartesian coordinates [18] ∂ t δT − D∇ 2 δT = −v∂ x T (11) where D = k/ρcp is the heat diffusion coefficient of the air, and ∂xT is the gradient of the stationary temperature distribution. The temperature perturbation caused by a single heating wire is derived…”
Section: Temperature Perturbation Due To the Acoustic Wavementioning
confidence: 99%
“…Recently, bio-inspired acoustic vector sensors (AVSs) have been demonstrated to detect the first-order spatial gradient of the pressure without any algorithms [5][6][7][8]. It has been shown that the AVSbased array can obtain higher directionality and a smaller array aperture than the microphone array [9][10][11]. * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…In [19], Biswas et al reported a metamorphic hemispherical microelectromechanical systems (MEMS) microphone array to estimate the location of a sound source in 3D space. In addition, Guo et al [20] introduced a 3 × 3 uniform rectangular array of 2D acoustic vector sensors with a miniaturized aperture to extract the directional acoustic modes. In [21], the authors designed a smallaperture differential microphone array and proposed a speaker direction-of-arrival (DOA) estimation method with orthogonal dipoles.…”
Section: Introductionmentioning
confidence: 99%
“…Especially recently, the interest in DOA estimation with VSA increased exponentially. Guo et al introduced a super directive mode domain beamformer for a 3 Â 3 uniform rectangular array of 2D acoustic VSA with miniaturized aperture [7]. Han and Nehorai applied the nested-array concept to VSA and provided a processing strategy for the source number detection and DOA estimation based on Higher Order Singular Value Decomposition (HOSVD) [8].…”
Section: Introductionmentioning
confidence: 99%